The Determinant Factors of Customer Satisfaction: Promotion, Service Quality and Brand Image - Aldilla Youthiana Oktavanny; Wahyu Sulistiadi (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The purpose of this study is to analyze the effect of promotion, service quality and brand image partially on customer satisfaction, and also to analyze which variables have dominant influence on customer satisfaction. Design/methodology/approach: The population in this study were 2,155 customers of RSUD Kertosono and the technique for determining the sample size was using the Slovin formula and obtained 96 people as sample. Questionnaire was used to obtain the data and data analysis technique used was Partial Least Square (PLS). Findings: The results indicated that promotion, service quality and brand image partially influence on customer satisfaction, and promotion had a dominant influence on customer satisfaction. Research limitations/implications: This research is limited to doing in RSUD Kertosono, East Java, Indonesia. For generalization so that further research can be carried out in different organizations or companies and in different regions (cities). Practical implications: The results of this research can be used as a reference to increase customer satisfaction in a hospital. Originality/value: The results of the research show that among the variables of promotion, service quality and brand image, promotion has a dominant influence on customer satisfaction. This is a new phenomenon that needs to be implemented in a hospital. Paper type: This paper can be categorized as research paper.